2023
DOI: 10.3390/children10050770
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Screen Time: The Different Longitudinal Relations between Adolescents’ Smartphone Use Content and Their Mental Health

Abstract: Purpose: Previous studies focusing on the relationship between adolescents’ screen time and mental health have uncovered contradictory results. By focusing on smartphone use content (SUC), this study uses specification curve analysis to explore the different effects of SUCs on mental health-based on longitudinal data. Methods: A total of 2552 adolescents were surveyed in the first (July 2020) and second year (April 2021). A total of 2049 eligible participants (average age = 14.39 ± 2.27, female = 1062) are inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Fifth, the high level of digital media use among children and adolescents is an ongoing concern. Although its use for educational purposes has also decreased since school closures and distance learning in South Tyrol [10,11], screen time for private purposes remains high and has been implicated as a significant predictor of mental health problems [43][44][45][46]. These non-pandemic-related items as well as sports behaviors were clearly associated with adolescents' mental health, suggesting that the best mental health outcomes are achieved by doing four or five days a week for at least 60 minutes of sports and using digital media for private concerns one hour or less per day.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the high level of digital media use among children and adolescents is an ongoing concern. Although its use for educational purposes has also decreased since school closures and distance learning in South Tyrol [10,11], screen time for private purposes remains high and has been implicated as a significant predictor of mental health problems [43][44][45][46]. These non-pandemic-related items as well as sports behaviors were clearly associated with adolescents' mental health, suggesting that the best mental health outcomes are achieved by doing four or five days a week for at least 60 minutes of sports and using digital media for private concerns one hour or less per day.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of longitudinal cross-lagged panel network data shows that the “conflict” in Short Video Addiction and the “sad mood” in depression may serve as bridge symptoms linking the co-occurrence of these two mental health issues ( Qu et al, 2024 ). However, there are other studies that did not find a robust relationship between watching short videos and psychopathological symptoms ( Huang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 96%
“…However, some studies have found that different ways of using mobile phones have different types of impact on mental health. For instance, recreational activities such as online gaming, watching TV, and listening to music appear to have a stronger impact on mental health, whereas online courses do not ( Huang et al, 2023 ). Previous studies related to mobile phone addiction mainly focused on issues regarding social networking.…”
Section: Introductionmentioning
confidence: 99%